KESULITAN BELAJAR TARUNA DALAM PEMBELAJARAN MATEMATIKA TEKNIK TERHADAP KETERAMPILAN PEMECAHAN MASALAH - FITRI Masito; Bambang Wijaya Putra; Minulya Eska Nugraha; Gunawan Sakti Nugraha; Ajeng Wulansari (Jurnal Penelitian)
The objectives to be achieved in this study are to find out the causes of cadets' learning difficulties in learning Engineering Mathematics and provide solutions to overcome cadets' learning difficulties in learning Engineering Mathematics. The approach in this study uses a qualitative descriptive approach. This research was carried out in the DIII Aviation Rescue and Fire Fighting Study Program at the Palembang Aviation Polytechnic. The data sources used are words and actions, photos, written data sources, and graphics. Methods of data collection using interviews, observation, and documentation. The sampling technique used is sampling with a sample of cadets. The results of this study obtained that the factors of learning difficulties for cadets in learning Engineering Mathematics were the lack of learning time, the lack of varied sample questions, the lack of learning resources, the lack of understanding of the material, and the absence of peer tutors. The solution in this research is to provide a collection of questions and how to solve them, add learning resources with books or modules, and appoint peer tutors as tutors when